Telisik Akar Penentu Integritas Laporan Keuangan - Ardiani Ika Sulistyawati; Lailatul Asna; Arief Himmawan Dwi Nugroho (Program Studi Manajemen Universitas Muslim Maros, 2022)
This study aims to analyze the effect of independent commissioners, managerial ownership, institutional ownership, audit committees, firm size and leverage on the integrity of financial statements in publicly listed manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique used in this study was purposive sampling, which obtained a sample of 120 companies with a research period of 4 years. The type of data used in this study uses secondary data in the form of financial statements of manufacturing companies. The analytical method used in this research is multiple linear regression analysis. The significance level used is 5%. The results of data analysis show that independent commissioners, managerial ownership, institutional ownership, and firm size affect the integrity of financial statements. Meanwhile, the audit committee and leverage have no significant effect on the integrity of the financial statements